Jenis-Jenis Ektoparasit pada Mamalia Kecil yang ditemukan di Pasar Raya Padang, Sumatera Barat - Beni Arengga; - Dahelmi; Siti Salmah (Jurnal Biologi Universitas Andalas, 2013)
A study about ectoparasites on the small mammals at Pasar Raya Padang, West Sumatera was conducted from November 2012 to January 2013. The purpose of this study was to know the species variety of ectoparasites on the small mammals. Present study used purpossive sampling method. The results showed that, two classes (Arachnida and Insecta), two orders (Acarina and Siphonaptera), three families (Sarcoptidae, Laelapidae and Pulicidae), and four species of ectoparasites (Echinolaelaps echidninus, Laelaps nuttalli, Sarcoptes scabiei and Xenopsylla cheopis) were found on two small mammal species (Rattus tanezumi and Suncus murinus). The highest number of individuals of ectoparasites was Echinolaelaps echidninus (46 individuals) and the lowest one was Sarcoptes scabiei (9 individuals).